Pengaruh tata kelola pemerintahan, efektivitas pengendalian internal, dan peran auditor internal terhadap tingkat kecurangan (studi pada satuan kerja perangkat daerah kabupaten kuantan singingi) - Rizke Wiliyanti; Ria Nelly Sari; Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study is to examine the effect of good governance,internal control effectiveness and the role of the internal auditor on the level of fraud.The population of this study were employees who worked in government agencies (27, agencies) in Kuantan Singingi regency. The sampling method used in this study is purposive sampling method. The data then analysed by using SPSS 18 software.The results prove that the effectiveness of internal controls and the role of internal auditors affect the level of fraud incidents. The magnitude of the effect (R2) of the good governance, effectiveness of internal control, and the role of the internal auditor on the level of fraud was 25,7%. While the remaining 74.3% is influenced by other variables.Keyword: good governance, internal control effectiveness, the role of the internal auditor, the level of fraud.